Pengembangan serta Pengimplementasian Sumber Daya Manusia dan Layanan Khusus di SMA Negeri 1 Taman Sidoarjo - Saputra, Dhani C; Sabilah, Rosyadatus; Safitri, Bunga Aurellia; Ramdhani, Oktafia Setia Ayu; Wulandari, Ayu (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
Human resources (HR) in the aspect of education have an important role in creating an effective and efficient educational environment. Special services in the school environment are intended to meet the needs of students, special services require cooperation between various elements of Human Resources, which include teachers, counselors, and health workers. This study aims to provide information to readers about Human Resources and special services at SMAN 1 TAMAN. Data collection techniques in this study used several techniques, namely, observation and interviews using primary data sources where data obtained by researchers directly from the source or first party through interviews and observations. In this qualitative research, the data analysis techniques used are data presentation and conclusion drawing. Presentation of data, namely researchers grouping the findings of observations and interviews to be presented and discussed in more detail in the form of narrative descriptive text. Furthermore, drawing conclusions is that researchers make conclusions based on the data provided by sources or from data sources in various analysis processes that have been carried out. The results show that proper training for teachers and support from school management, as well as student involvement can affect the effectiveness of special services. In addition, a continuous evaluation system is also key in tailoring special services to students' needs. This research is expected to provide recommendations for the development of a more responsive education policy at SMAN 1 Taman.